Individual behavior of gas hydrodynamics from pairs of isolated galaxies in interaction - Teofilo-Salvador Eduardo (St. Petersburg Polytechnical University Journal: Physics and Mathematics)
The hydrodynamic behavior of the gas of a selected pair of interacting galaxies has been reviewed based on numerical simulation using Illustris and IllustrisTNG. 210 halos were identified visually, using the Explorer; but their number was reduced due to selection taking into account found distances, masses and particle emission conditions, then the halos were refined and received specific cuts using Python. Among them, 34% did not interact at all, due to asymmetries ranging from 18 to 74%. The pair with ID 473420-473421 turned out to be the best interacting pair, and it was most marked at z = 1 and 5. This sample provided more information about the behavior of the gas present, such as the formation of tidal tails, with a relative velocity of 9 to 213 km/s. The density fields were affected by distribution velocities and radial motion in galaxy interaction processes, the gas flow created transitions between the two disks in the radial velocity field, with longer jets in regions of cold gas compared to those of hot one.